1994
DOI: 10.1098/rspb.1994.0041
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of the family Camelidae: a mitochondrial DNA study

Abstract: We report the first molecular evolutionary analysis of the family Camelidae by analysing the full DNA sequence of the mitochondrial cytochrome b gene. Estimates for the time of divergence of the Old World (Camelini) and New World (Lamini) tribes obtained from sequence data are in agreement with those derived from the fossil record. The DNA sequence data were also used to test current hypotheses concerning the ancestors of the domesticated llama and alpaca. The results show that hybridization has occurred in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(32 citation statements)
references
References 25 publications
1
26
1
4
Order By: Relevance
“…The phylogenetic a¤liations of the llama and alpaca were ¢rst con¢rmed by sequencing a short (158 bp) but highly informative region of the cytochrome b gene of the mitochondrial genome sensu Stanley et al (1994) (GenBank accession numbers U06425^U06430). In total, 211 South American camelids were analysed from throughout the geographical range (comprising 21 guanaco, 42 vicu·a, 54 llama, 84 alpaca and the 10 hybrids described in table 1).…”
Section: (B) Mtdna Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The phylogenetic a¤liations of the llama and alpaca were ¢rst con¢rmed by sequencing a short (158 bp) but highly informative region of the cytochrome b gene of the mitochondrial genome sensu Stanley et al (1994) (GenBank accession numbers U06425^U06430). In total, 211 South American camelids were analysed from throughout the geographical range (comprising 21 guanaco, 42 vicu·a, 54 llama, 84 alpaca and the 10 hybrids described in table 1).…”
Section: (B) Mtdna Analysismentioning
confidence: 99%
“…DNA samples were stored in TE bu¡er (10 mM Tris-HCl, 1mM EDTA, pH 8.0). The cytochrome b primers L14724 and H14900 were used for polymerase chain reaction (PCR), which was carried out as in Stanley et al (1994). PCR products were puri¢ed and DNA sequencing was carried out as previously described (Stanley et al 1994).…”
Section: (B) Mtdna Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…This was the first viable hybridization between the Old and New world camelids , and the result of 50 attempts to produce a cross between species that diverged 11 million years ago (Stanley et al, 1994). Jones et al (2000) suggested that glycan-glycan interactions at the fetomaternal interface may play a role in successful implantation and subsequent maintenance of pregnancy, and that interspecies differences in glycosylation may be one mechanism for blocking inappropriate hybridization.…”
Section: Introductionmentioning
confidence: 99%